Mothers’ Nutritional Knowledge, Self-efficacy, and Practice of Meal Preparation for School-age Children in Yangon, Myanmar - Phyo, Wut Yee; Khin, Ohn Khin; Aung, Min Htike (Makara Journal of Health Research, 2021)
Background: Childhood malnutrition is a global public health concern. For Myanmar, mothers play a prominent role in improving the nutritional status of children as they prepare meals for children. Methods: This community-based cross-sectional analytical study was conducted on 367 mother-child pairs (6–10 years). Significantly, systematic random sampling and structured questionnaires were utilized in this study. Results: The mean age of mothers was 35.73 ± 6.9 years, and a majority had fair nutritional knowledge (52.3%), good self-efficacy (79.8%), and good practice of meal preparation (59.4%). The prevalence of childhood malnutrition was categorized as stunting (18.2%), underweight (18.8%), wasting (13.3%), overweight (9.0%), and obesity (6.5%). Only 34.2% of children were in the normal nutritional status. The nutritional knowledge of mothers was associated with the age and education of mothers, child ownership, monthly food budget, and height-for-age (p < 0.05). Mothers’ self-efficacy was associated with education, child ownership, monthly food budget, height-for-age, and weight-for-age (p < 0.05). The meal preparation practice of mothers was associated with their education, child ownership, monthly food budget, height-for-age, and BMI-for-age (p < 0.05). Nutritional knowledge, self-efficacy, and meal preparation practice of mothers were strongly correlated with each other (p < 0.001). BMI-for-age was associated with mothers’ education (p < 0.05). Conclusions: This study suggests improving the nutritional aspects of mothers by providing nutrition education combined with self-efficacy improving activities. This activity will lead to maintaining good nutrition in school-aged children.